2007
DOI: 10.1111/j.1527-3466.2007.00010.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and Role of the Presynaptic and Myocardial Na+/H+ Exchanger NHE1: Effects on the Sympathetic Nervous System in Heart Failure

Abstract: In acute myocardial ischemia and in chronic heart failure, sympathetic activation with excessive norepinephrine (NE) release from and reduced NE reuptake into sympathetic nerve endings is a prominent cause of arrhythmias and cardiac dysfunction.The Na + /H + exchanger NHE1 is the predominant isoform in the heart. It contributes to cellular acid-base balance, and electrolyte, and volume homeostasis, and is activated in response to intracellular acidosis and/or activation of guanine nucleotide binding (G) protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…*P Ͻ 0.05. perfusion with veratridine leads to a massive reduction of NET activity, with a small amount of release of [ 3 H]NE. This is in line with data that have shown that NET function is dependent from the intracellular Na ϩ gradient (38) and, at least during acute changes of intracellular pH and ATP as observed during, e.g., ischemia-reperfusion, from the presynaptic Na ϩ /H ϩ exchanger (38). However, the aim of the present study was to investigate the chronic effects of a HS diet over several weeks.…”
Section: Discussionsupporting
confidence: 47%
“…*P Ͻ 0.05. perfusion with veratridine leads to a massive reduction of NET activity, with a small amount of release of [ 3 H]NE. This is in line with data that have shown that NET function is dependent from the intracellular Na ϩ gradient (38) and, at least during acute changes of intracellular pH and ATP as observed during, e.g., ischemia-reperfusion, from the presynaptic Na ϩ /H ϩ exchanger (38). However, the aim of the present study was to investigate the chronic effects of a HS diet over several weeks.…”
Section: Discussionsupporting
confidence: 47%
“…content [6]. The NHE1 activity contributes to cardiac hypertrophy [61,65,66,100]. Accordingly, cardiac hypertrophy and its progression to heart failure can be strongly reduced by NHE1 inhibitors [1,24,60].…”
Section: Discussionmentioning
confidence: 98%
“…The cardiac Nhe1 has emerged as a key factor in myocardial remodeling [65,66,67]. Enhanced Nhe1 activity contributes to the pathophysiology of myocardial reperfusion injury [68], cardiac insufficiency [69] and cardiac hypertrophy [42,43,70,71,72]. Accordingly, upregulation of Nhe1 may trigger [73] and pharmacological inhibition of Nhe1 counteracts [65,66,67] cardiac hypertrophy and progression to heart failure.…”
Section: Discussionmentioning
confidence: 99%